2005
DOI: 10.14310/horm.2002.11154
|View full text |Cite
|
Sign up to set email alerts
|

Hypoparathyroidism in a patient presenting with severe myopathy and skin rash. Case report and review of the literature

Abstract: A 47-year old man with idiopathic hypoparathyroidism (IHP), presented as severe myopathy and skin rash is described. The serum muscle enzymes were increased. After treatment with calcium and vitamin D, the clinical condition improved, the skin rash gradually disappeared, and the muscle enzymes decreased and remained within the normal range thereafter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Serum CK levels may be increased secondary to muscle damage from sustained tetany. Hyporeflexia or areflexia is usually present and contrasts with the hyperreflexia in hyperparathyroidism (Syriou et al, 2005). …”
Section: Step 1: Overview and Understanding Of Myopathies In Systemicmentioning
confidence: 99%
“…Serum CK levels may be increased secondary to muscle damage from sustained tetany. Hyporeflexia or areflexia is usually present and contrasts with the hyperreflexia in hyperparathyroidism (Syriou et al, 2005). …”
Section: Step 1: Overview and Understanding Of Myopathies In Systemicmentioning
confidence: 99%
“…Thus, previous studies suggest that hypocalcemia may cause myopathy (16, 17), while hypercalcemia in hyperparathyroidism impairs gait speed (18). We have previously reported that fluctuations in plasma calcium levels occurred, which occasionally resulted in mild hypercalcemia among patients of the therapy group with intact PTH (11).…”
Section: Discussionmentioning
confidence: 98%
“…90,92,97,98 In a few cases, evidence of myopathy including early recruitment of motor units was described. 89,93 Similarly, muscle biopsies were normal in some cases 85,88,96,98 while other cases showed various changes consistent with mild, non-specific myopathy including atrophic and/or necrotic muscle fibers, internal nuclei, and inflammatory cell infiltrate. 89,[91][92][93]97 Notably, all reported cases were in patients with marked hypocalcemia, and therapeutic increase of serum calcium levels led to a decrease in muscle enzymes in all cases with normalization in most.…”
Section: Hypoparathyroidism-associated Myopathymentioning
confidence: 96%
“…89,93 Similarly, muscle biopsies were normal in some cases 85,88,96,98 while other cases showed various changes consistent with mild, non-specific myopathy including atrophic and/or necrotic muscle fibers, internal nuclei, and inflammatory cell infiltrate. 89,[91][92][93]97 Notably, all reported cases were in patients with marked hypocalcemia, and therapeutic increase of serum calcium levels led to a decrease in muscle enzymes in all cases with normalization in most. In two particularly illustrative cases, patients intermittently discontinued calcium therapy; CPK levels rose in concert with the fall in serum calcium and then decreased with resumption of therapy.…”
Section: Hypoparathyroidism-associated Myopathymentioning
confidence: 96%
See 1 more Smart Citation